Parental child care time, income and subjective well-being: A multidimensional polarization approach for Germany - Joachim Merz; Normen Peters (Leuphana Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 2019)
Neither market income nor consumption expenditure provides an adequate picture of individual standard of living. It is time which enables and restricts individual activities and is a further brick to a more comprehensive picture of individual wellbeing. In our study we focus on a prominent part of time use in non-market services: it is parental child care which contributes not only to individual but also to societal well-being. Within a novel approach we ask for multidimensional polarization effects of parental child care where compensation/ substitution of time for parental child care versus income is interdependently evaluated by panel estimates of society's subjective well-being. The new interdependent 2DGAP measure thereby provides multidimensional polarization intensity information for the poor and the rich and disentangles the single time and income contribution to subjective well-being ensuring at the same time the interdependence of the polarization dimensions. Socio-economic influences on the polarization pole risk and intensity will be quantified by two stage Heckman estimates. The analyses are based on the German Socio-Economic Panel with 21 waves and robust fixed effects estimates of subjective well-being as well as the German Time Use Surveys 1991/92 and actual 2012/13 with detailed diary time use data. The empirical results discover the interdependent relations between parental child care and income under a common evaluation frame and contribute to the question of dimension specific targeted policies in a multidimensional polarization approach. Prominent result: compensation between parental child care time and income proved to be significant, but there are multidimensional regions with no compensation, where parental child care time deficit is not compensated by income. Interdependent multidimensional polarization by headcount and intensity increased significantly over the twenty years under investigation with remarkable risk and intensity differences between the polarization poles with different disentangled parental child care time and income contributions to subjective well-being.
Keywords: I31; I32; J22; D10; D31; 330; parental child care; multidimensional polarization of interdependent time and income; subjective well-being; poverty and affluence; minimum multidimensional 2DGAP risk and intensity; German Socio-Economic Panel (SOEP); German Time Use Study (GTUS 1991/92 and 2012/13); Elterliche Kinderbetreuung; multidimensionale Polarisierung interdependenter Zeit und Einkommen; subjektive Wohlfahrt; Armut und Reichtum; minimales multidimenionale 2DGAP Risiko und Einkommen; deutsches Sozioökonomisches Panel (SOEP); deutsche Zeitbudgetsurveys (GTUS 1991/92 und 2012/13)